2010
DOI: 10.1186/1472-698x-10-16
|View full text |Cite
|
Sign up to set email alerts
|

Efficiency of the health extension programme in Tigray, Ethiopia: a data envelopment analysis

Abstract: BackgroundSince 2004, the government of Ethiopia has made a bold decision to strengthen and expand its primary health care system by launching the Health Extension Program (HEP). While the scaling up of the HEP is necessary to achieve the aim of universal access to primary health care, close attention should be paid to the performance of the program. Using a data envelopment analysis this study aimed at (i) to estimate the technical efficiency of a sample of health posts in rural Tigray, ii) to identify those … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
57
3
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(66 citation statements)
references
References 18 publications
5
57
3
1
Order By: Relevance
“…Despite encouraging reports of positive impact of HEP, 8,[22][23][24][25][26]52 the findings of this study show major deficiency in its overall performance. The scores across all domains were low, which could be due to their interdependence, where the capacity for service provision and financial systems influence the human resource development, the community engagement and service provision process that in turn affect the output and outcome dimension.…”
Section: Discussioncontrasting
confidence: 84%
See 3 more Smart Citations
“…Despite encouraging reports of positive impact of HEP, 8,[22][23][24][25][26]52 the findings of this study show major deficiency in its overall performance. The scores across all domains were low, which could be due to their interdependence, where the capacity for service provision and financial systems influence the human resource development, the community engagement and service provision process that in turn affect the output and outcome dimension.…”
Section: Discussioncontrasting
confidence: 84%
“…6,32,39 Although it used few indicators, a study by Sebastian and others found that the performance of HEP was poor and that there was inefficiency in productivity relative to available resources, which is an indication that multidimensional factors other than inputs affect the outcome of the program. 8 The BSC approach used in this article helped identify health system elements with relatively poor performance. 14,16 The performance of the program was low in the areas of infrastructure, commodity (including financing, distribution and availability), satisfaction and perception of HEWs, infection prevention, referral linkage, and service quality and outputs.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In 2003, the Government of Ethiopia launched the Health Extension Programme to develop a body of salaried basic-level health-care providers -health extension workers (HEWs) -who could increase the availability and coverage of basic health services for Ethiopia's large rural population. 22,23 While HEWs have been an innovative addition to the Ethiopian health sector, their ability to conduct community outreach varies depending on the time demanded by the wide range of health interventions for which they are responsible. Another group of workers composed of volunteers known as community-based reproductive health agents (CBRHAs) was initially mobilized to provide basic family planning services and referrals, although they have acquired more responsibilities in the community and often support the activities of the HEWs.…”
Section: Introductionmentioning
confidence: 99%